2007
DOI: 10.1002/cncr.22807
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of 18F‐fluorodeoxyglucose positron emission tomography (18F‐FDG‐PET) and a comparison of 18F‐FDG‐pet with 67gallium scintigraphy in the evaluation of lymphoma

Abstract: BACKGROUND.Although studies comparing conventional imaging modalities with 18F‐fluorodeoxyglucose positron emission tomography (18F‐FDG‐PET) for the detection of lymphoma and although the relations between 18F‐FDG‐PET and histologic types were reported previously, most studies were not systematic and involved relatively small numbers of patients.METHODS.Two hundred fifty‐five patients with lymphoma had their disease staged using 18F‐FDG‐PET, and 191 of those patients also were assessed using gallium‐67 scintig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
7

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(114 citation statements)
references
References 34 publications
5
101
1
7
Order By: Relevance
“…16 However, the intensity of uptake (ie, a higher SUV) is typically highest in DLBCL and lower in follicular lymphoma and mantle cell lymphoma. Indolent lymphomas such as small lymphocytic lymphoma and splenic marginal zone lymphoma are less FDG-avid, and FDG-PET may be less likely to detect sites of active disease.…”
Section: Which Lymphomas Yield Abnormal Results On Pet Scan?mentioning
confidence: 99%
See 1 more Smart Citation
“…16 However, the intensity of uptake (ie, a higher SUV) is typically highest in DLBCL and lower in follicular lymphoma and mantle cell lymphoma. Indolent lymphomas such as small lymphocytic lymphoma and splenic marginal zone lymphoma are less FDG-avid, and FDG-PET may be less likely to detect sites of active disease.…”
Section: Which Lymphomas Yield Abnormal Results On Pet Scan?mentioning
confidence: 99%
“…Indolent lymphomas such as small lymphocytic lymphoma and splenic marginal zone lymphoma are less FDG-avid, and FDG-PET may be less likely to detect sites of active disease. 16 Less is known about FDG-PET in T-cell lymphomas, but FDG-PET results are positive in most T-cell lymphomas except indolent cutaneous T-cell lymphoma. [17][18][19] Although PET scans may be useful in identifying sites of disease, some studies have suggested that FDG-PET may not be predictive of outcome in certain histologic subtypes.…”
Section: Which Lymphomas Yield Abnormal Results On Pet Scan?mentioning
confidence: 99%
“…FL is a (18)F-FDG avid disease, since more than 90% of patients with FL show a PET positive disease and sensitivity of staging PET is usually higher than 95% [6][7][8][9]. Published literature includes 10 retrospective analyses [9][10][11][12][13][14][15][16][17][18] and 1 prospective one [19]: pooled analysis of 356 patients revealed that 24% were upstaged from Stage I-II to Stage III-IV.…”
Section: Issue 1: Staging (Consensus-based Recommendations)mentioning
confidence: 99%
“…For this purpose, strict pretreatment evaluation incorporating positron emission tomography [65][66][67][68][69][70][71] and in situ hybridization for EBVencoded RNA using a bone marrow specimen [72] are recommended. As chemotherapeutic regimens for ENKL are evolving, a new prognostic model among patients treated with chemotherapies without anthracycline is needed.…”
Section: For the Better Future Management Of Enklmentioning
confidence: 99%